Structural, Optical and Surface Properties of Sol-Gel Spin Coated Al Doped ZnO Thin Films - Senthamizhselvi*, M.; Sankara Subramanian, N.; Rajathi, S. (Asian Journal of Chemistry, 2013)
Undoped and aluminium doped zinc oxide (ZnO:Al, AZO) thin films have been prepared at different heat treatment temperatures (300 to 400 ºC) onto mineral glass substrates by sol-gel spin coating method. The XRD profile of all the films confirm the hexagonal wurtzite structure with preferred orientation along the (002) plane. The average particle size evaluated from the XRD profile lies in between 15 nm and 25 nm. The other crystallographic parameters namely, lattice strain, dislocation density, texture coefficient and standard deviation have been estimated and reported. The optical transmittance of the aluminium doped zinc oxide film heat treated at 350 ºC exhibits a maximum of 85 % at the wavelength 800 nm. The band gap energy of the aluminium doped zinc oxide films evaluated from the optical transmittance measurement lies between 3 and 3.1 eV. The AFM image of the aluminium doped zinc oxide film heat treated at 350 ºC shows uniform surface pattern with nano sized particles. The effect of heat treatment temperature on the properties of spin coated aluminium doped zinc oxide thin films has been analyzed and elaborated.